The clinical profile and outcome of patients receiving continuation electroconvulsive therapy (C-ECT): A retrospective study - Sandeep Grover; Sanjana Kathiravan; Subho Chakrabarti (Indian Journal of Psychiatry, 2023)
Background: There is a lack of data on the use of continuation electroconvulsive therapy (C-ECT) from India. Objectives: This study aimed to evaluate the clinical profile and outcome of patients receiving C-ECT. Materials and Methods: The ECT register was used to identify patients receiving C-ECT (ECT after completion of an acute course, to maintain remission or prevent relapse) from 2011 to July 2022. Socio-demographic, clinical, and treatment outcome details were extracted from their treatment records. Results: A total of 72 C-ECT courses were identified that were used in 60 patients. Out of all the patients receiving ECT, only 3.25% of patients receive C-ECT. The majority of the patients were male (60%). The mean age of the patients at the time of starting ECT was around 39 years. The most common diagnosis was schizophrenia (73.3%), followed by recurrent depressive disorder (21.6%). The most common indication was persistent psychotic symptoms poorly responding to multiple antipsychotic trials of 3.09 (SD: 1.39), including clozapine. These patients received a mean of 22.58 (SD: 8.05; range: 10 to 46) ECTs, with 10.0 (SD: 4.83) ECTs for the management of the acute phase of illness and 12.57 (SD: 6.20) ECTs as part of continuation treatment. The majority (61.1%) of the patients received four (once weekly) C-ECTs in the first month, followed by three more in the next month. However, 16 patients received weekly ECTs during the second month too, as symptoms worsened with the lowering of frequencies. Twelve patients received more than one C-ECT course. The majority of the patients maintained the improvement gained during the acute phase or showed further improvement with C-ECT along with ongoing pharmacotherapy as rated on appropriate scales. The Clinical Global Impressions-Severity (CGI-S) difference before and after C-ECTs was 2.94 (SD: 0.88). Conclusions: C-ECT is considered in only in a small proportion of patients. However, when used, it is effective in maintaining the benefits gained during the acute course of ECT and preventing relapse.